Gender Diversity and Female Employees at Company X A Case study Exploring Challenges at Company X and Initiatives Aimed Towards Women - Soumi, Gabriella (My University, 2024)
The construction industry still struggles with an underrepresentation of women, and stereotypes persist despite efforts to break them down. Company X is no exception to this trend. This thesis aims to explore the experiences of female employees at Company X, focusing on the challenges they encounter and what influences their decision to stay with the company. It also assesses their awareness and attitudes towards existing support initiatives, as well as the effectiveness of the company's strategies for attracting and retaining female talent. Additionally, the research seeks to identify areas for improvement and propose new initiatives to promote gender diversity, inclusion, and retention within Company X. A thorough literature review was conducted to gather relevant information, and existing initiatives within Company X and other organizations were examined to provide context. Furthermore, qualitative interviews were conducted with female employees at Company X to gain insight into their perspectives and experiences. The results revealed a variety of viewpoints and experiences among women at Company X. The result together with the literature review and existing initiatives, helped analysis the current challenges and motivational factors at Company X, as well as initiatives to attract women to Company X but also initiatives aimed towards the women there. From this further improvements into the existing initiatives could be made as well as suggest new initiatives worth developing. The analysis also helped point out the challenges women face at Company X for them to be able to work against them.
Keywords: Construction industy; gender diversity; gender stereotypes; female employees; challenges; intiatives; inclusion; retention; harassment